Gambaran struktur kulit hewan coba pada beberapa interval waktu postmortem - Abeng, Kartika A.; Kalangi, Sonny J. R.; Wangko, Sunny (Universitas Sam Ratulangi, 2016)
Abstract: This study aimed to obtain the postmortem histological changes of the skin. This was an experimental-descriptive study using one pig as model. Samples were taken at several time intervals during 24 hours postmortem: 0 hour; 1 hour; 2 hours; 3 hours; 4 hours; 5 hours; 6 hours; 7 hours; 8 hours; 9 hours; 10 hours; 11 hours; 11 hours; 12 hours; and 24 hours. The results showed that histological changes of the skin began to occur in 4 hours postmortem in the form of epidermal congestion. In 5 hours postmortem Meissner corpuscles could not be identified anymore. In 7 hours postmortem most cells of epidermis showed karyolysis. In 8 hours postmortem Langerhans cells could not be identified anymore. In 9 hours postmortem structure epidermal cells can not be identified. In 24 hours postmortem, borders of the epidermis and dermis could not be identified. Conclusion: Postmortem changes in the histological structure of the skin were consecutively: epidermal congestion, Meissner corpuscles and Langerhans cells could not be identified, and karyolysis of epidermal cells. In 24 hours postmortem, most of the skin architecture was unidentified. It is expected that these postmortem histological changes of the skin could be applied in the medicolegal investigation especially for death cases of less than 24 hours postmortem, therefore, further studies are needed.Keywords: structure, skin, postmortemAbstrak: Penelitian ini bertujuan untuk mendapatkan perubahan gambaran histologik kulit postmortem. Penelitian ini menggunakan metode deskriptif eksperimental dengan babi sebagai hewan coba. Sampel jaringan kulit diambil pada interval waktu 0 jam; 1 jam; 2 jam; 3 jam; 4 jam; 5 jam; 6 jam; 7 jam; 8 jam; 9 jam; 10 jam; 11 jam; 12 jam; dan 24 jam postmortem. Hasil penelitian memperlihatkan perubahan struktur mulai tampak 4 jam postmortem berupa kongesti epidermis kulit. Pada 5 jam postmortem badan Meissner tidak dapat diidentifikasi lagi. Pada 7 jam postmortem sebagian sel-sel epidermis mulai kariolisis. Pada 8 jam postmortem sel Langerhans tidak dapat diidentifikasi lagi. Pada 9 jam postmortem struktur sel-sel epidermis tidak dapat diidentifikasi. Pada 24 jam postmortem batas epidermis dan dermis tidak dapat diidentifikasi. Simpulan: Perubahan struktur kulit postmortem yang dimulai pada 4 jam postmortem ialah sebagai berikut: kongesti epidermis, badan Meissner dan sel Langerhans tidak dapat diidentifikasi, dan kariolisis sel-sel epidermis. Pada 24 jam postmortem arsitektur kulit telah menjadi tidak tegas. Penelitian ini diharapkan dapat diaplikasikan untuk kepentingan medikolegal, terutama pada kematian â‰¤24 jam.Kata kunci: struktur histologik kulit, postmortem